COMMUNICATIONS IN THE PROCESS OF MANAGEMENT OF SOCIALLY RESPONSIBLE ACTIVITIES OF THE ENTERPRISE (Development Service Industry Management, 2024)
The article considers the role of communications in the process of socially responsible activity of the enterprise. The authors researched two main components of the enterprise's social responsibility: internal and external. Internal responsibility contributes to the formation of a strong and loyal team, focused on achieving results and ready to support social initiatives. External responsibility increases the company's reputation, helps attract new customers and partners, and also contributes to the establishment of sustainable relations with the public. The aspects on which the concept of social responsibility of the enterprise is based are highlighted, among which communication has a significant influence. Through transparent communication, the company demonstrates its commitment to the principles of social responsibility, which increases the trust of customers, partners and the community. This approach contributes to the formation of a positive reputation, attracting new customers and strengthening relations with existing ones. It has been proven that the communication task is one of the key ones in the context of social responsibility of business, as effective communications contribute to the establishment of open and transparent relations between the company and stakeholders. It is substantiated that an important aspect of the communication task is taking into account the interests of various stakeholders when making management decisions, which helps to avoid conflicts and ensure the harmonious development of both the business and the community in which it operates. Effective communication strategies allow the enterprise to convey information about its social initiatives to the public, environmental projects, ethical standards and contribution to the development of society. The authors indicate that communication becomes an important tool for brand formation, which supports the values of social responsibility and promotes long-term relations between the enterprise and society.
Keywords: communication; social responsibility; communicative task; charity; social responsibility of business